Readings in International Accounting (Book). - Sterling, Robert R.; Senn, Alan R. (The Accounting Review, 1970)
Reviews the book "Readings in International Accounting," by Kenneth B. Berg and Gerhard G. Mueller and Lauren M. Walker.